Captopril usage in determining myocardial viability on a nuclear ventriculography - Amalia Peix González; David García Barreto; Felizardo Ponce Vicente; Adlin López Díaz; Ana Ma. Maltas Pineda (ECIMED, 2014)
In order to diagnose myocardial viability in infarct patients with depressed ventricular function, we used the vasodilator effect of Captopril in a nuclear ventriculography. 14 cases with an ejection fraction of the left ventricle at rest < 50 % were studied. All the patients underwent a nuclear ventriculography (before and after Captopril 25 mg intake, v.o.) and a scintigraphy of myocardial perfussion with thallium-201 and reinjection. The ejection fraction increased from 38 " 10 % to 42 " 12 % (p < 0.01) with Captopril. Systolic blood pressure decreased from 132 " 24 mm of Hg to 126 " 27 mm of Hg (p < 0.05). Diastolic blood pressure, heart rate and ventricular volumes were not significantly modified after Captopril intake. The same viability diagnosis was obtained by means of ventriculography and scintigraphy in 11 of the 14 patients studied. In conclusion, nuclear ventriculography with Captopril can be a useful and economic alternative method to diagnose myocardial viability in infarct patients with depressed contractile function.